Ultrasmall particles for Gd‐MRI and 68Ga‐PET dual imaging. (5th December 2014) - Truillet, Charles; Bouziotis, Penelope; Tsoukalas, Charalambos; Brugière, Jérémy; Martini, Matteo; Sancey, Lucie; Brichart, Thomas; Denat, Franck; Boschetti, Frédéric; Darbost, Ulrich; Bonnamour, Isabelle; Stellas, Dimitris; et al.
<x xml:space="preserve">Abstract</x> Nanoparticles made of a polysiloxane matrix and surrounded by 1, 4, 7, 10‐tetraazacyclododecane‐1‐glutaric anhydride‐4, 7, 10‐triacetic acid (DOTAGA)[Gd3+] and 2, 2'‐(7‐(1‐carboxy‐4‐((2, 5‐dioxopyrrolidin‐1‐yl)oxy)‐4‐oxobutyl)‐1, 4, 7‐triazonane‐1, 4‐diyl)diacetic acid) NODAGA[68Ga3+] have been synthesized for positron emission tomography/magnetic resonance (PET/MRI) dual imaging. Characterizations were carried out in order to determine the nature of the ligands available for radiolabelling and to quantify them. High radiolabelling purity (>95%) after 68Ga labelling was obtained. The MR and PET images demonstrate the possibility of using the nanoparticles for a combined PET/MR imaging scanner. The images show fast renal elimination of the nanoparticles after intravenous injection.Copyright © 2014 John Wiley & Sons, Ltd.